Practical knowledge of heavy medical examination bed designs (Al-Academy, 2026)
The research is concerned with studying the utilization of heavy medical examination bed designs. The research problem was identified in the difficulties facing the design and use of heavy medical examination beds, as traditional medical beds suffer from shortcomings in meeting the needs of this category. These difficulties include poor ability to bear high weights, lack of comfort for the patient, and difficulty of use for healthcare providers. Many current designs also lack the utilization knowledge that ensures the integration of functions with ease of use, which affects the quality of the medical service provided and the safety of both the patient and the doctor. The theoretical framework included two chapters. The first chapter was entitled: The nature of utilization knowledge in medical examination beds. While the second chapter was determined in: The extent of design suitability of medical examination beds. The research reached the most important results, which are that the models were distinguished by technology in functional and aesthetic performance, and the product contained advanced performance characteristics and levels, and allowed the recipient to accept and be satisfied and achieve the goal in using the models (1-2-3). It was achieved thanks to the high technical level by (100%) of the research samples, and the most important conclusions were that the technology in the medical family for advanced examination was based on its use functionally and easily and technically in the kinetic and fixed performance and taking comfort and safety in performing the function and the response of use within the type of that function very well